PRESENT-DAY TITANOMACHY OR THE NATURE OF ENERGY GEOPOLITICS IN CENTRAL ASIA - MADINOV, Elnur (CENTRAL ASIA AND THE CAUCASUS, 2007)
After fifteen years of development the outlines of the new international system remain rather vague mainly because international cooperation (dominated by the globalizing economy) has not yet acquired definite features and the leading international actors are still readjusting their foreign policies. These processes have already affected the foreign policy of most states and their ideas about geopolitical strategy in today’s dynamic world. Rapid economic development in the world’s leading countries requires an ever-larger amount of energy resources (oil, gas, coal, uranium, etc.), which has already affected the nature of international politics: political systems are growing increasingly dependent on energy sources and transportation routes. We are living in a world where those who produce energy sources, those who transport them, and those who use them occupy the main niches. Recently, this hierarchy acquired another, and most important, structural element: the mighty powers resolved to keep the entire energy chain under their control and influence the geopolitical processes in every corner of the world by deciding were the energy sources should be moved. Energy geopolitics and its central formula, “he who controls the energy sources controls the World,” have come to the fore as one of the geopolitical pivots. After all, the energy issue is indispensable for continued secure and sustainable development.